Accelerated Orthodontic Canine Retraction Using Minimally Invasive Orthocision - Omar Chawshli; Zana Omer; Omed Ikram (Erbil Dental Journal)
Background and objectives: The contemporary demand for an accelerated orthodontic treatment associated with the disadvantage of complicated and difficult surgical procedures and corticotomies. The aim of this study was to evaluate the more conservative orthocision technique as a way for accelerating orthodontic treatment.